2018
DOI: 10.1186/s13550-018-0400-x
|View full text |Cite
|
Sign up to set email alerts
|

Detection of neuroinflammation before selective neuronal loss appearance after mild focal ischemia using [18F]DPA-714 imaging

Abstract: BackgroundTranslocator protein (TSPO) imaging can be used to detect neuroinflammation (including microglial activation) after acute cerebral infarction. However, longitudinal changes of TSPO binding after mild ischemia that induces selective neuronal loss (SNL) without acute infarction are not well understood. Here, we performed TSPO imaging with [18F]DPA-714 to determine the time course of neuroinflammation and SNL after mild focal ischemia.ResultsMild focal ischemia was induced by middle cerebral artery occl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 43 publications
(51 reference statements)
2
14
0
Order By: Relevance
“…In a very clinically relevant model of focal temporary MCAO using a minimally invasive technique through the insertion of a microwire tip via the ventral tail artery, Toth et al [83] demonstrated significant increases in [ 11 C]PBR28 uptake in the infarct at day 4, 7 and 14 post-MCAO, although [ 11 C]PBR28 uptake started to decrease at day 14. Their results are in line with other studies using more conventional models of stroke in rats [76,65] such as those developed by Miyajima et al [84] described a significant increase in [ 18 F]DPA-714 uptake in the infarct from day 2 maintained up to day 7 post-MCAO (20-min intraluminal MCAO). Taken altogether, these results confirmed that in these models of acute brain injury (permanent or temporary MCAO, SAH or hypoxia), the microglial/macrophage infiltration responsible for the TSPO increase takes approximately 3 days to become detectable, peaks about 1 week after injury and then slowly decreases in intensity afterwards.…”
Section: Strokesupporting
confidence: 91%
“…In a very clinically relevant model of focal temporary MCAO using a minimally invasive technique through the insertion of a microwire tip via the ventral tail artery, Toth et al [83] demonstrated significant increases in [ 11 C]PBR28 uptake in the infarct at day 4, 7 and 14 post-MCAO, although [ 11 C]PBR28 uptake started to decrease at day 14. Their results are in line with other studies using more conventional models of stroke in rats [76,65] such as those developed by Miyajima et al [84] described a significant increase in [ 18 F]DPA-714 uptake in the infarct from day 2 maintained up to day 7 post-MCAO (20-min intraluminal MCAO). Taken altogether, these results confirmed that in these models of acute brain injury (permanent or temporary MCAO, SAH or hypoxia), the microglial/macrophage infiltration responsible for the TSPO increase takes approximately 3 days to become detectable, peaks about 1 week after injury and then slowly decreases in intensity afterwards.…”
Section: Strokesupporting
confidence: 91%
“…Miyajima et al. 172 monitored [ 18 F] 15 uptake with PET imaging and found that it was markedly increased before selective neuronal loss (SNL) in an ischemic stroke rat model, a change that was also observed by ex vivo autoradiography. Tan et al.…”
Section: Development Of Radioligands Targeting Tspomentioning
confidence: 88%
“…Stoke rapidly induces necrosis of all cells within the infarct; however, two types/locations of delayed neuronal death after brain ischemia have also been identified (Figure 1). ( 1) 'Selective neuronal loss' may occur in peri-infact areas 1-7 days after transient middle cerebral artery occlusion (MCAO) in rodent striatum (and to a lesser extent in the cortex), but may increase over the following weeks [4,[7][8][9][10][11][12][13]. (2) 'Secondary neurodegeneration' of the thalamus may occur 0.5-12 months after cortical stroke [2,3,14].…”
Section: Types Of Neuronal Death After Strokementioning
confidence: 99%